Answer:
The correct answer is D.) y = -2x-3
Step-by-step explanation:
You can solve the given equation y - 5 = -2(x + 4):
y - 5 = -2(x + 4) simplify the right side
y - 5 = -2x - 8 add 5 to both sides
y = -2x - 3
<u><em>Hope it helps! have a great day! :)</em></u>
Step-by-step explanation:
Laurie read x+1/3 pages.
Mia read x pages.
Answer: 6:15
Step-by-step explanation:
Answer:
is the last one
Step-by-step explanation:
Answer:
Dividing each part into 10 and then summing the results up, is equivalent to dividing 89.5 into 10.
Step-by-step explanation:
This example refers to the Distributive Property of the division, which is valid when the dividend is decomposed.
A simple example could be: 400 ÷ 10 = (200 ÷ 10) + (200 ÷ 10)
In the exposed example we know that 89.5 = 80 + 9 + 0.5.
(80/10) + (9/10) + (0.5/10) =
8 + 0.9 + 0.05=
8.95
89.5/10 = 8.95